Failure analysis of adhesively bonded cfrp joints - Daylan, Seda (Graduate School, 2021)
Joints are critical areas where load transfer occurs and should be designed to provide maximum strength to the structure. The adhesive bonding process is widely used as a structural joining method in aerospace applications. There are many advantages of using adhesively bonding joints instead of classical mechanical fastening. Some of these can be listed as joining of similar and dissimilar materials (metal-to-composite, metal-to-metal, metal-to-glass), providing a more uniform stress distribution with a significant decrease in the stress concentration in the structure since there will be no fastening holes, a considerable weight gain compared to mechanical fasteners, strong in terms of fatigue strength due to the absence of fastener holes in the structure. In addition to the above-mentioned positive aspects of using adhesives as a structural joining method, strength prediction is vital for an optimum design process in the initial sizing and critical design phases. The fact that adhesively bonded joints have various failure modes makes failure predictions complex. According to ASTM D5573, adhesively bonded composite joints have seven typical failure modes, but they can be listed under three main headings: adhesive failure, cohesive failure, and adherend failure. Adhesive failure occurs at the adherend and adhesive interface, and usually, the adhesive remains on an adherend. These failures are generally attributed to the poor-quality bonding process, environmental factors, and insufficient surface preparation. The other kind of failure, adherend failure, occurs when the structural integrity of the adherend breaks down before the joint structure and means that the strength of the joint area exceeds the strength of the adherend. On the other hand, cohesive failure is the type of failure expected after an ideal design and bonding process, where failure occurs within the adhesive structure. After cohesive failure, the adhesive material is seen on both adherends. Structural joining with adhesive has been used in the aerospace industry since the early 1970s and 1980s. Since these dates, many analytical and numeric methods have been used to study the failures of adhesively bonding joints. Analytical method studies to analyze the failures of adhesively bonded single lap joints, known in the literature, started with Volkersen in 1938. Volkersen did not include the eccentricity factor in the calculations due to the geometric nonlinearity of the single lap joint. This factor was first taken into account by Goland and Reissner in their calculations in 1944. Goland and Reissner made a remarkable study in analysing the adhesively bonded single lap joint, calculating the loads in the joint area and subsequently the stress on the adhesive. Afterwards, analytical method studies were continued by Hart Smith, Allman, Bigwood & Crocombe and more. In addition to analytical method studies, the continuum mechanic approach, fracture mechanic approach, and damage mechanic approach can be given examples to the numerical method studies. The fracture mechanics approach used in this thesis examines the initial crack propagation in the adhesive under three different loading modes. Crack propagation occurs when the adhesive's critical strain energy release rate equals the strain energy release rate under that load. After the three different modes' strain energy release rate values are calculated separately, an evaluation is made according to the power-law failure criterion. There are many types of joint configurations in the literature, and the common ones can be summarized as single lap joints, double lap joints, stepped joints etc. The single-lap joint type is the most widely used joint type in terms of ease of design and effectiveness. Within the scope of this thesis, it is aimed to obtain a general solution that can be applied to all joints after first making a study for the single lap joint geometry and validating the results of this study experimentally. Studies have been carried out to predict the failure load of adhesively bonding CFRP joints. They include two main steps, which are to find the loads at the edges of the joint area and to evaluate the failure criteria by calculating the strain energy release rate with these loads. As the first step, loads at the joint edges are found analytically and with the finite element method, respectively. While calculating the loads analytically, the Modified Goland and Reissner theory is used, which differs from the classical Goland and Reissner theorem by taking the adhesive thickness into account. While calculating the loads with the finite element method, the modelling technique first studied by Loss and Kedward and then described by Farhad Tahmasebi in his work published with NASA is used. The primary purpose of using this modelling technique is to simulate load transfers in overlap regions accurately for complex and analytically challenging to calculate geometries. Especially in aerospace, since modelling the large components with solid elements is not effective in terms of time and resources, a practical modelling technique that can produce results with high accuracy is needed. In the modelling technique used in the thesis, adherends are modelled with shell elements while the adhesive region is modelled between coincident nodes with three spring elements to provide stiffnesses in the shear and peel directions, and the nodes of the adhesive elements are connected to the adherends with rigid elements. The modulus values of the adhesive material are used in the stiffness calculation of the spring elements. After obtaining the loads with the analytical and finite element method, the second step, the calculation of the strain energy release rate values on the adhesive material, is carried out with reference to two different studies. Firstly, linear fracture mechanics formulations were studied by Williams, assuming that the energy required to advance an existing crack unit amount is equal to the difference of performed external work with internal strain energy, and the laminate containing crack performs linear elastic behaviour is used. Conventional beam theory is used for the 1D case, as the deformation will occur like beam deformation. Using beam theory, he formulated the external work and internal strain energy at the beginning and end of the crack. And using these two equations, he found energy release rate formulations in relation to bending moment and axial load. Then, mode separation is made to calculate the energy release rates in the mode I and II directions separately because the critical strain energy release rate value in these two directions is different and needs to be evaluated independently. This study's disadvantage is that the transverse shear load is ignored, and calculations are made only with bending moment and longitudinal force. Within the scope of the thesis, the strain energy release rate is calculated both with the loads found analytically and with the loads found by the finite element method. Shahin and Taheri did the other reference work, and with overlap edge loads, the stress on the adhesive first and then the strain energy release rate is calculated. In this study, two assumptions are made, and the first is that the shear and peel stress change is zero along with the thickness of the adhesive, and the other is that the stress on the adhesive is as much as the displacement difference of the adherends. As a result of the derivations, the stress distribution on the adhesive is found in the joint structure consisting of CFRP adherend and adhesive. Then, according to Irwin's VCCI approach, as if there is a virtual crack, the integration crack length is rewritten so that it converges to zero and the displacements are in stress. Thus, the stress and energy relationship equation is obtained, and strain energy release rates in mode I and II directions of the adhesive are calculated. As a result of all these studies, mode I and mode II strain energy release rate calculations are made according to two different methods with the loads found analytically and with the finite element method. The strain energy release rate values found and the critical strain energy release rate values, which are allowable, are evaluated according to the power-law failure criteria, and failure load predictions are made. For specimens with different overlap lengths, experimental failure load values and predicted failure load values are compared, and inferences are made about the accuracy of the FEM modelling technique and the methods used in SERR calculation. All these results are interpreted in detail, and it is obtained that the FEM modelling technique gives high accuracy results with Method 2 used in SERR calculation. Finally, a bonding analysis tool has been developed with the python programming language. This tool first detects the finite elements corresponding to upper and lower adherends in the model from NASTRAN .bdf file. Then reads the element loads from the .pch file, which is a NASTRAN output and contains the element loads, then calculates the SERR using Method 2 and calculates the reserve factor and failure load, respectively. This tool has been prepared so that these calculations can be made in a short time and accurately for tens of elements in the overlap zone in complex and large models.
Yapıştırmalı kompozit bağlantıların hasar analizi
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2021
Keywords: Damage analysis; Hasar analizi; Composites; Kompozitler; Agglutinate; Yapıştırma; Adhesive links; Yapıştırmalı bağlantılar